Determinants of Banks’ Stability: A Case Study of Banks Listed on The Ghana Stock Exchange - Dwamena Kofi; Oscar Agyemang Opoku; Henry Okudzeto (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The study was to analysed the determinants of stability of banks listed on the Ghana Stock Exchange (GSE). The study used 8 of the 9 banks listed on the Ghana Stock Exchange for the study. The study used annual data of the sampled banks on the GSE from 2015 to 2019. Panel regression analysis was used to unravel the determinants of bank stability in Ghana. The study found that Income diversity, the size of a bank, inflation, regulation and gross domestic product do not determine the stability of banks listed on the Ghana Stock Exchange (GSE). A weak positive relationship was found between income diversity, the size of a bank, inflation, regulation and gross domestic product and the stability of banks listed on the Ghana Stock Exchange. The study concluded that income diversity, size of a bank, inflation rate in the country, the gross domestic product do not determine the stability of banks listed on the Ghana Stock Exchange. The study makes the following recommendations. Future studies to be conducted into the determinants of bank stability using variables. The Bank of Ghana (BoG) and other bodies to pay more attention to other factors other than size, income diversity, inflation, regulation, gross domestic product in their bid to enhancing banking stability as these factors do not affect the stability of banks in Ghana